The elephant whisperer : my life with the herd in the African wild - Anthony, Lawrence (Thomas Dunne Books/St. Martin's Press, 2009)
It had been nearly a century since elephants had lived in Southern Zululand, South Africa, where Lawrence Anthony founded his Thula Thula wildlife reserve. Yet one day a phone call changed all that. A troubled, unpredictable herd needed a new home. In order to save their lives, Lawrence took them in, and in the years that followed found that they had a lot to teach him about life, loyalty, and freedom. He tells of hair-raising fights with poachers, of elephants as surprise dinner guests, of raising a baby elephant in his home, and other stories.--From publisher description.